Online sentence processing impairments in agrammatic and logopenic primary progressive aphasia: Evidence from ERP. (22nd January 2021) - Barbieri, Elena; Litcofsky, Kaitlyn A.; Walenski, Matthew; Chiappetta, Brianne; Mesulam, Marek-Marsel; Thompson, Cynthia K.
Abstract: Evidence from psycholinguistic research indicates that sentence processing is impaired in Primary Progressive Aphasia (PPA), and more so in individuals with agrammatic (PPA-G) than logopenic (PPA-L) subtypes. Studies have mostly focused on offline sentence production ability, reporting impaired production of verb morphology (e.g., tense, agreement) and verb-argument structure (VAS) in PPA-G, and mixed findings in PPA-L. However, little is known about real-time sentence comprehension in PPA. The present study is the first to compare real-time semantic, morphosyntactic and VAS processing in individuals with PPA (10 with PPA-G and 9 with PPA-L), and in two groups of healthy (22 young and 19 older) individuals, using event-related potentials (ERP). Participants were instructed to listen to sentences that were either well-formed (n = 150) or contained a violation of semantics (e.g., * Owen was mentoring pumpkins at the party, n = 50), morphosyntax (e.g., *The actors was singing in the theatre, n = 50) or VAS (*Ryan was devouring on the couch, n = 50), and were required to perform a sentence acceptability judgment task while EEG was recorded. Results indicated that in the semantic task both healthy and PPA groups showed an N400 response to semantic violations, which was delayed in PPA and older (vs. younger) groups. Morphosyntactic violations elicited a P600 in both groups of healthy individuals and in PPA-L, but not in PPA-G. A similar P600 response was also found only in healthy individuals for VAS violations; whereas, abnormal ERP responses were observed in both PPA groups, with PPA-G showing no evidence of VAS violation detection and PPA-L showing a delayed and abnormally-distributed positive component that was negatively associated with offline sentence comprehension scores. These findings support characterizations of sentence processing impairments in PPA-G, by providing online evidence that VAS and morphosyntactic processing are impaired, in the face of substantially preserved semantic processing. In addition, the results indicate that on-line processing of VAS information may also be impaired in PPA-L, despite their near-normal accuracy on standardized language tests of argument structure production. Highlights: Online sentence processing is impaired in Primary Progressive Aphasia. N400s to semantic violations are preserved in logopenic and agrammatic subtypes. P600s to morphosyntactic violations are abnormal in the agrammatic subtype. Abnormal P600s to verb-argument structure violations are found in both subtypes.